The Influence Of Health Education On The Impact Of Electronic Cigarettes (Vape) With Audiovisual Media On Knowledge Of The Dangers Of Electronic Cigarettes Among Youth Communities In The Depok Area In 2025 - Indy Nurrohmah Indy Nurrohmah; Emi Yuliza; Saiful Gunar (CV. AFDIFAL MAJU BERKAH, 2026)
The prevalence of e-cigarettes in Indonesia increased by 3% in 2021 according to the Ministry of Health's GATS, with a high knowledge gap among adolescents in Depok due to modern lifestyle trends. This study aims to determine the effect of health education on the dangers of vaping using audiovisual media on adolescent knowledge. A quasi-experimental one-group pretest-posttest design was conducted on a population of 50 adolescents in RT 07 Sukamaju Depok, with a sample of 20 respondents via purposive sampling. The Guttman scale questionnaire instrument was analyzed using univariate frequency and bivariate Kolmogorov-Smirnov post-normality t-test (p=0.072). The results showed a decrease in knowledge from less than 60% to 30%, an increase from sufficient to 40% to 55%, and good from 0% to 15%, with p=0.013. Audiovisual education is effective in significantly increasing adolescent knowledge.